Antipsychotic polypharmacy and clozapine prescribing patterns: evolution and correlates before and after a psychiatric hospitalisation. (July 2022) - Lagreula, Juliette; de Timary, Philippe; Elens, Laure; Dalleur, Olivia
Background: Antipsychotic polypharmacy (APP) prescribing and clozapine underuse are considered inappropriate prescribing in schizophrenia. Psychiatric hospitalisations may be suitable occasions to re-evaluate patient pharmacotherapy and to switch to monotherapy. Objectives: To explore the evolution of APP and other psychotropic prescribing patterns during psychiatric hospitalisations, to detect characteristics associated with APP on admission and at discharge, and to examine clozapine prescribing patterns. Design: We performed a retrospective observational study based on electronic health records. Methods: Data on adult inpatients diagnosed with schizophrenia spectrum disorders were collected retrospectively from 6 Belgian hospitals in 2020-2021. Results: Of the 516 patients included, APP prescribing increased significantly from 47.9% on hospital admission to 59.1% at discharge. On admission and at discharge, APP was associated with prior clozapine use (ORadmission = 2.53, CI = 1.1–5.84, ORdischarge = 11.01, CI = 4.45–27.28), treatment with a first-generation antipsychotic (ORadmission = 26.79, CI = 13.08–54.86, ORdischarge = 25.2, CI = 12.2–52.04), increased antipsychotic exposure (ORadmission = 8.93, CI = 5.13–15.56, ORdischarge = 19.89, CI = 10–39.54), and a greater number of hypno-sedatives (ORadmission = 1.88, CI = 1.23–2.88, ORdischarge = 4.18, CI = 2.53–6.91). APP was negatively associated with involuntary admission (ORadmission = 0.31, CI = 0.14–0.7, ORdischarge = 0.3, CI = 0.13–0.68). When using an alternative definition of monotherapy (i.e. including patients with an add-on low-dose antipsychotic for sleep disorders), alcohol use disorder (ORadmission = 0.26, CI = 0.13–0.54) and higher age (ORdischarge = 0.53, CI = 0.29–0.95) were negatively associated with APP, and living in a residential facility (ORdischarge = 2.39 CI = 1.21–4.71) and a higher daily dosage of benzodiazepines during the stay (ORdischarge = 1.32 CI = 1.03–1.69) increased the odds of being discharged on APP. On admission, 9.3% of patients were being treated with clozapine. Although 28.1% of patients were eligible for clozapine treatment, only 11% of patients were discharged with a clozapine prescription. For 7 of the 10 patients with a new clozapine prescription, it was directly prescribed in combination with another antipsychotic, without a prior trial of clozapine monotherapy. Conclusion: Suboptimal prescriptions of antipsychotics in patients with schizophrenia persist after psychiatric hospitalisations and are associated with identifiable characteristics.